Design of a tidal turbine array for the Bohai Strait, China - Chen, L; Bonar, PAJ; Adcock, TA (American Society of Mechanical Engineers, 2018)
In this paper, we consider array design strategies to maximise the power available to turbines placed in the Bohai Strait, which is considered to be one of China’s most promising candidate sites for tidal stream power. The discontinuous Galerkin version of the open-source hydrodynamic model ADCIRC is used to simulate flow through the strait and tidal turbines are introduced using a sub-grid scale actuator disc model. New design algorithms based on key theoretical results are used to build large arrays, which are then compared in terms of both the collective power output and the power produced per turbine. The results of the analysis are used to draw general conclusions about the optimal design of tidal turbine arrays.